Investigating the Sensitivity and Specificity of Fine Needle Aspiration Cytology for Diagnosing Malignant Liver Tumors - Paheli Maru; Vibha R Vyas; Varnika Rai; Shilpa Kapoor; Samanta Satarupa (Journal of Medical Sciences and Health)
Background: The liver is a common site for malignant tumors, both primary and secondary. An early and accurate diagnosis can help in the clinical management of these tumors. Fine needle aspiration cytology (FNAC) is a minimally invasive procedure that aids in an earlier diagnosis than a biopsy. Aims and Objectives: 1) The main objective of the present study was to establish the adequacy and accuracy of FNAC in diagnosing malignant liver tumors in a tertiary cancer institute, 2) To analyze inconclusive and inadequate aspirations and find out diagnostic pitfalls. Materials and Methods: A total of 406 patients underwent image-guided percutaneous FNAC and biopsy sampling of liver mass lesions from 2018–2020. Hematoxylin, eosin, and May-Grünwald-Giemsa stains were examined. Statistical analyses were performed using histological diagnoses from liver biopsy samples as the gold standard to ascertain the sensitivity, specificity, and accuracy of FNAC in the diagnosis of liver lesions. Results: Among the 406 aspirations received over a period of three years, 364 (90%) were adequate, 30 (7%) were inconclusive and 12 (3%) were inadequate. Among the positive aspirations, primary hepatic malignancies were 69 (20%) and secondary malignancies were 230 (63%), the most common being gastrointestinal primaries. The sensitivity, specificity, accuracy, positive predictive value and negative predictive value of FNAC in diagnosing malignant liver lesions in our center were 87.25%, 71.21% and 22.72% respectively. Paucicellularity, repeated aspirations from the necrotic area and aspiration of reactive hepatocytes in the vicnity of metastasis were the most frequent diagnostic errors. Conclusion: Fine needle aspiration cytology is a cost-effective and precise diagnostic method for both primary and secondary malignant liver cancers. It should be incorporated as a point of care in personalized medicine.